Kinetics of severe acute respiratory syndrome coronavirus 2 infection antibody responses - Lin, Yajie; Zhu, Jiajie; Liu, Zongming; Li, Chaonan; Guo, Yikai; Wang, Ying; Chen, Keda (Frontiers in Immunology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread rapidly throughout the world, causing severe morbidity and mortality. Since the first reports of Coronavirus disease 2019 (COVID-19) in late 2019, research on the characteristics of specific humoral immunity against SARS-CoV-2 in patients with COVID-19 has made great progress. However, our knowledge of persistent humoral immunity to SARS-CoV-2 infection is limited. The existence of protective immunity after infection will affect future transmission and disease severity. Therefore, it is important to gather knowledge about the kinetics of antibody responses. In this review, we summarize the information obtained so far on the characteristics and kinetics of the SARS-CoV-2 infection of specific humoral immune response, especially in neutralizing antibodies and their relationship with disease severity. In addition, with the emergence of variants of concern, we summarize the neutralizing effect of specific humoral immunity on variants of concern after the initial SARS-CoV-2 infection and vaccination.